2016
DOI: 10.1007/s00406-016-0721-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired executive control and reward circuit in Internet gaming addicts under a delay discounting task: independent component analysis

Abstract: This study utilized independent component analysis to explore the abnormal functional connectivity (FC) in male participants with Internet gaming disorder (IGD). Functional magnetic resonance imaging and behavioral data were collected from 21 healthy controls (HC) and 18 IGD patients when they were performing a delay discounting task. Behavioral results revealed that the IGD patients showed higher delay discounting rates than HC. Two networks were found to be associated with IGD: (1) the executive control netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 81 publications
5
45
1
Order By: Relevance
“…In Experiment III, we found that the vmPFC and the dlPFC in participants with addiction did not contain information that reflected the specific choice, and that the decoding accuracy from both the vmPFC in patients with Internet‐gaming disorder and the dlPFC in smokers were significantly lower than those in healthy participants. Consistent with previous studies showing altered brain activity in the dlPFC in smokers and participants with Internet gaming disorder (Clewett et al, ; Wang et al, ), our results highlight the important role of dlPFC in addiction from the perspective of activity patterns. Our data also support the concept that, in terms of addictions, intact vmPFC function is important during value representation (Bedi, Lindquist, & Haney, ; Qi et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Experiment III, we found that the vmPFC and the dlPFC in participants with addiction did not contain information that reflected the specific choice, and that the decoding accuracy from both the vmPFC in patients with Internet‐gaming disorder and the dlPFC in smokers were significantly lower than those in healthy participants. Consistent with previous studies showing altered brain activity in the dlPFC in smokers and participants with Internet gaming disorder (Clewett et al, ; Wang et al, ), our results highlight the important role of dlPFC in addiction from the perspective of activity patterns. Our data also support the concept that, in terms of addictions, intact vmPFC function is important during value representation (Bedi, Lindquist, & Haney, ; Qi et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that there was a significant relationship between the discounting rate and decoding accuracy in the left dlPFC in patients with Internet‐gaming disorder as well as in smokers. Previous studies have shown that higher impulsivity in patients with addiction is correlated with altered functional connectivity of the dlPFC (Clewett et al, ; Wang et al, ). Our data confirmed the critical role of the dlPFC in the impulsive behaviour of individuals with addiction.…”
Section: Discussionmentioning
confidence: 97%
“…Several neuroimaging researches have examined the impaired executive control ability indexed by dysfunction or structural abnormalities in ACC in people with IGD (Dong et al, 2011a, 2013a; Zhou et al, 2011; Wang et al, 2015; Dong and Potenza, 2016), as well as in drug addiction and pathologic gambling (Ruiter et al, 2011; Moeller et al, 2013; Santangelo et al, 2013; Schmidt et al, 2014; Feng et al, 2015). Better control ability in recreational online game users than online game addicts are associated with enhanced activation in ACC in a decision-making task (Wang Y. et al, 2016b). Combined with these findings, the present result may reveal a deficient executive control ability in IGD subjects, accompanied with comparably better control ability in RGU subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been noted that IGD subjects are associated with failures in controlling the desire for playing online games (Lin et al, 2015a). Numerous imaging studies have found impaired executive control ability in IGD subjects (Dong and Zhou, 2010; Dong et al, 2010, 2011b, 2012a, 2014b, 2015, 2017b; Dong and Potenza, 2014; Weinstein and Lejoyeux, 2015; Wang L. et al, 2016a,b; Wang Y. et al, 2016b; Weinstein et al, 2017), yet, the direct evidence for the impaired executive control ability in inhibiting craving for game-playing in the context of online gaming cues are still lacking (Ko et al, 2008, 2013; Han et al, 2010; Sun et al, 2012). Thus, the present study filled in the gap.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by previous works, SC-FC coupling was generally considered to represent the degree of neuroanatomical constraint over functional brain dynamics, thus determining the capacity of robust reconfigurations for distributed network organization pattern (Griffa et al, 2015;van den Heuvel et al, 2013). Of note, the failure to resist the temptation of attractive immediate reward, to a large extent, could be attributed to the impaired cognitive function, particularly to executive control ability (Sasse, Peters, & Brassen, 2017;Wang et al, 2017). Of note, the failure to resist the temptation of attractive immediate reward, to a large extent, could be attributed to the impaired cognitive function, particularly to executive control ability (Sasse, Peters, & Brassen, 2017;Wang et al, 2017).…”
Section: Coupling Of Structural-functional Connectivity On Intertemmentioning
confidence: 99%